Femtosecond laser shock peening of ultra-thin-walled Ti-6Al-4V: study on surface integrity and high cycle fatigue mechanism - Rongping Wang; Xinbin Zhang; Peng He; Wenhe Wang; Wenhua Chen; Xiaolong Wei; Xinlei Pan; Liucheng Zhou (Journal of Materials Research and Technology)
Ultra-thin-walled structural components are widely used in aeroengines, but they are prone to high-cycle fatigue (HCF) failure due to cyclic alternating stresses during operation. While various surface treatment technologies have been developed to address this challenge, issues such as excessive macroscopic deformation due to limited machining precision remain unresolved. To improve the surface integrity and fatigue resistance of ultrathin-walled Ti–6Al–4V titanium alloys, this study innovatively regulates the energy and impact numbers of femtosecond laser shock peening (FLSP) technology. By controlling the deformation to within 0.15 mm, the fatigue limit of the material was successfully increased by 15.2 %. This improvement is attributed to the generation of a high-amplitude compressive residual stress (CRS) layer approximately 100 μm deep at the surface. Microstructural evolution and dislocation behavior analysis revealed that a single femtosecond laser shock peening (FS-1) significantly refined the grain structure and increased dislocation density, while triple femtosecond laser shock peening (FS-3) reduced dislocation density through a dynamic recrystallization (DRX) recovery mechanism. The uniform stress field induced by FLSP promoted crack initiation in the subsurface layer, and the multi-scale fracture features formed by FS-3 effectively reduced crack propagation and enhanced energy dissipation, further improving fatigue resistance. This work provides a novel technological approach and theoretical guidance for surface strengthening of ultra-thin-walled components.